Glacier elevation change in the Western Qilian mountains as observed by TerraSAR-X/TanDEM-X images. Issue 12 (21st July 2021) - Zhang, Qibing; Kang, Shichang
Abstract: The glaciers in the Qilian mountains are a major water resource for the arid Hexi corridor and Qaidam basin. With the climate becoming warmer and wetter, it is essential to study the glacier elevation changes in this region. We used TerraSAR-X/TanDEM-X images, SRTM DEM data and differential synthetic aperture radar interferometry (DInSAR) technology to analyse the glacier elevation change. Results show that the glacier elevation is changing at the rate of –0.35 m yr −1 in the western Qilian mountains between 2000 and 2014. The glacier elevation thinning at –0.40 m yr −1 in the southern part of this region is more severe than that in the northern part (–0.29 m yr −1 ). The long-term equilibrium line altitude, calculated from glacier elevation change in each elevation bin, was at 5150 m, which is equal to that inferred from glacial area distribution in each elevation bin. Glacier shrinkage is related to air temperature increasing.